2008
DOI: 10.1093/rheumatology/ken116
|View full text |Cite
|
Sign up to set email alerts
|

Diacerein has a weak effect on the catabolic pathway of human osteoarthritis synovial fibroblast--comparison to its effects on osteoarthritic chondrocytes

Abstract: Diacerein does not seem to reduce but rather increase inflammatory mediators in synoviocytes, while it does not overall affect chondrocyte inflammatory profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
2
30
0
2
Order By: Relevance
“…Further, in equine synoviocytes transduced with an adenoviral vector carrying a coding region for IRAP, MMP13 mRNA expression was significantly lower compared to non-transduced controls 8 . Interestingly, however, one study evaluating diacerein did not detect a significant difference in MMP13 in media of human OA chondrocytes stimulated by rhIL-1β (10 U/ml), but differences in experimental design may account for this discrepancy 9 . Reduction of iNOS mRNA and NO release from bovine chondrocytes 10 , human OA chondrocytes in alginate beads 11 , and LPS-stimulated (1 mg/ml) human OA cartilage 12 have also been observed following application of diacerein/rhein in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Further, in equine synoviocytes transduced with an adenoviral vector carrying a coding region for IRAP, MMP13 mRNA expression was significantly lower compared to non-transduced controls 8 . Interestingly, however, one study evaluating diacerein did not detect a significant difference in MMP13 in media of human OA chondrocytes stimulated by rhIL-1β (10 U/ml), but differences in experimental design may account for this discrepancy 9 . Reduction of iNOS mRNA and NO release from bovine chondrocytes 10 , human OA chondrocytes in alginate beads 11 , and LPS-stimulated (1 mg/ml) human OA cartilage 12 have also been observed following application of diacerein/rhein in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…The neutrophils when performing phagocytosis of MSU induce phagolysosomes which are destabilized by the crystals producing the generation of ROS, cytokine release, proteases, products of arachidonic acid, prostaglandins, and myeloperoxidase [41], triggering membrane disruption and cell death, as well as extracellular trap formation, that are composed of loosened chromatin and granule proteins such as neutrophil elastase, cathepsin G, and lactotransferrin. An active cell death mechanism is distinct from apoptosis and necrosis and depends on the production of ROS by NADPH oxidase, Schorn et al in 2012 identified neutrophils, eosinophils, and basophils as capable to externalize nuclear DNA after incubation with MSU [42].…”
Section: Oxidative Stress Mechanisms In Goutmentioning
confidence: 99%
“…Surprisingly, diacerein inhibited IL-1β-stimulated NF-κB activation in synoviocytes and chondrocytes, but increased cyclooxygenase-2 (COX-2) protein expression and PGE 2 synthesis [Pelletier et al 1998;Sanchez et al 2003;Alvarez-Soria et al 2008]. The impact of this PGE 2 overexpression induced by diacerein needs to be clarified, particularly on joint tissue neovascularization.…”
Section: Nsaidsmentioning
confidence: 99%